Infographic. The effect of high-speed running on hamstring strain injury risk - Duhig, S. J.; Shield, A. J.; Opar, D.; Gabbett, T. J.; Ferguson, C.; Williams, M. (British Journal of Sports Medicine, 2019)
Australian rules football is a challenging contact sport requiring high levels of fitness and skill. In the last two decades, hamstring strain injuries have remained an ongoing problematic issue, constituting a large proportion of soft tissue injuries sustained in the elite Australian Football League (AFL). The predominant injury mechanism for hamstring strain injuries is sprinting.